2012
DOI: 10.4238/2012.september.17.4
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial DNA variants and copy number in diabetic atherogenesis

Abstract: ABSTRACT. Hyperglycemia-induced reactive oxygen species production can cause diabetes and its complications, including atherosclerosis. The role of mitochondrial DNA variants and mitochondrial copy number in the pathogenesis of diabetic atherogenesis is not well understood. We examined 36 diabetic patients who had undergone amputation for diabetic foot and seven non-diabetic patients who had undergone amputation after traumatic injury. Mitochondrial DNA was extracted and used for sequencing. Single nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In our previous study, we found that diabetic atherogenesis is associated with decreased levels of mtDNA (Chien et al, 2012). The results of the present study showed that although HMGB1 may act as an inflammatory mediator based on its positive correlation with the expression of oxidative stress markers (8-OHdG and MDA), a proinflammatory marker (VCAM-1), and inflammatory markers (CD3 and CD68) both in the intima and the media of vessels, an HMGB1-related compensation mechanism may also function in diabetic patients with PAOD.…”
Section: Discussionmentioning
confidence: 91%
“…In our previous study, we found that diabetic atherogenesis is associated with decreased levels of mtDNA (Chien et al, 2012). The results of the present study showed that although HMGB1 may act as an inflammatory mediator based on its positive correlation with the expression of oxidative stress markers (8-OHdG and MDA), a proinflammatory marker (VCAM-1), and inflammatory markers (CD3 and CD68) both in the intima and the media of vessels, an HMGB1-related compensation mechanism may also function in diabetic patients with PAOD.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, mtDNA copy number is a key functional parameter that varies greatly between different cell or tissues types, both in response to overall metabolic and bioenergetics demands and as a consequence or cause of specific physiological and pathological conditions. Alterations in mtDNA copy number have been related to aging (He et al, 2014), cancer , neurodegenerative diseases (Podlesniy et al, 2013), diabetes (Chien et al, 2012) and other mitochondrial-related diseases (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…72 Diabetes is one of the major risk factors for atherosclerosis, and there is a report that diabetic atherogenesis is associated with decreased mtDNA copy number. 73 …”
Section: Consequences Of Excessive Mtrosmentioning
confidence: 99%